Hemopoiesis indices in patients with diabetes type II with and without vascular complications - Bondar Т.Р.; Anfinogenova O.I.; Bondar M.V.; Soldatov А.А. (Саратовский научно-медицинский журнал, 2010)
The article presents data of 1470 case histories and laboratory findings of 290 patients with diabetes and 82 donors who have done such procedure for the first time. Changes of morphological and biophysical indices of erythrocytes, thrombocytes and leukocytes are determined. The analysis of laboratory findings among patients with diabetes complicated by vascular disorders, with diabetes without complications and healthy representatives of the investigation has been carried out. It has revealed significant changes in indices